Association of Digoxin Application Approaches With Long-Term Clinical Outcomes in Rheumatic Heart Disease Patients With Heart Failure: A Retrospective Study - Liu, Cheng; Lai, Yanxian; Guan, Tianwang; Zeng, Qingchun; Pei, Jingxian; Zhang, Shenghui; Wu, Daihong; Wu, Deping (Frontiers in Cardiovascular Medicine, 2021)
Objective: This retrospective, case-control study was executed to assess the effects of digoxin (DGX) use approaches [continuous use of DGX (cDGX) vs. intermittent use of DGX (iDGX)] on the long-term prognosis in rheumatic heart disease (RHD) patients with heart failure (HF). Methods: A total of 642 RHD patients were enrolled to this study after propensity matching. The associations of DGX application approaches with the risks of all-cause mortality, cardiovascular death (CVD), HF re-hospitalization (1-year, 3-year and 5-year) and new-onset atrial fibrillation (AF) were analyzed by multivariate Cox proportional hazards or binary logistic regression models, respectively. Results: cDGX was associated with increased risks of all-cause mortality (adjusted HR=1.84, 95% CI: 1.27-2.65, P=0.001) and CVD (adjusted HR=2.23, 95% CI: 1.29-3.83, P=0.004) in RHD patients with HF compared to iDGX. With exception of 1-year HF re-hospitalization risk, cDGX was associated with increased HF re-hospitalization risk of 3-year (adjusted OR=1.53, 95% CI: 1.03-2.29, P=0.037) and 5-year (adjusted OR=1.61, 95% CI: 1.05-2.50, P=0.031) as well as new-onset AF (adjusted OR=2.06, 95% CI: 1.09-3.90, P=0.027). Conclusion: cDGX was significantly associated with increased risks of all-cause mortality, CVD, medium-/long-term HF re-hospitalization, and new-onset AF in RHD patients with HF.